Peningkatan Kualitas Layanan di Era Digital: Peran Mediasi Kompetensi Karyawan pada Hubungan Kapabilitas Digital terhadap Keunggulan Layanan di Hotel Bintang Tiga Bandung Barat - Antonius Iskandar Yahya; Raden Intan Medya Ratna Pury (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to analyze the effect of digital capability on service excellence through employee competence as a mediating variable in three-star hotels in West Java. This research employs a quantitative approach with a survey method. Data were collected from 220 hotel employees and analyzed using Structural Equation Modeling based on Partial Least Square (SEM-PLS) with SmartPLS software. The results indicate that digital capability significantly affects employee competence. Digital capability also significantly affects service excellence. Employee competence significantly influences service excellence. Furthermore, employee competence partially mediates the relationship between digital capability and service excellence. These findings highlight that digital transformation in the hospitality industry depends not only on technology but also on human resource readiness in optimizing technology to enhance service quality.